Assessing the impact of the National Agricultural Advisory Services (NAADS) in the Uganda rural livelihoods - Benin, Samuel; Nkonya, Ephraim M.; Okecho, Geresom; Pender, John L.; Nahdy, Silim; Mugarura, Samuel; Kayobyo, Godfrey (International Food Policy Research Institute, 2007)
The National Agricultural Advisory Services (NAADS) program of Uganda is an innovative public-private extension service delivery approach, with the goal of increasing market oriented agricultural production by empowering farmers to demand and control agricultural advisory services. Although initial evaluations of NAADS have been quite favourable, these evaluations have been primary qualitative in nature. This study quantifies the initial impacts of NAADS in the districts and sub-counties where the program was operating by 2005. It is based on descriptive analyses of results of a survey of 116 farmer groups and 894 farmers in sixteen districts where the program was operating at the time and four districts where NAADS had not yet begun operating to control for factors that may have contributed to differing initial conditions among the communities. Based on observed differences across the NAADS and non-NAADS sub-counties, it appears that the NAADS program is having substantial positive impacts on the availability and quality of advisory services provided to farmers, promoting adoption of new crop and livestock enterprises as well improving adoption and use of modern agricultural production technologies and practices. NAADS also appears to have promoted greater use of post-harvest technologies and commercial marketing of commodities, consistent with its mission to promote more commercially-oriented agriculture. Despite positive effects of NAADS on adoption of improved production technologies and practices, no significant differences were found in yield growth between NAADS and non-NAADS sub-counties for most crops, reflecting the still low levels of adoption of these technologies even in NAADS sub-counties, as well as other factors affecting productivity. However, NAADS appears to have helped farmers to avoid the large declines in farm income that affected most farmers between 2000 and 2004, due more to encouraging farmers to diversify into profitable new farming enterprises such as groundnuts, maize and rice than to increases in productivity caused by NAADS. NAADS appears to be having more success in promoting adoption of improved varieties of crops and some other yield enhancing technologies than in promoting improved soil fertility management. This raises concern about the sustainability of productivity increases that may occur, since such increases may lead to more rapid soil nutrient mining unless comparable success in promoting improved soil fertility management is achieved. Continued emphasis on improving the market environment, promoting adoption of more remunerative crop enterprises, and applied agronomic research identifying more effective ways to profitably combine inorganic and organic soil fertility measures in different crop systems can help to address this problem. Shortage of capital and credit facilities was often cited by farmers as a critical constraint facing them, in addition to scarcity of agricultural inputs, lack of adequate farmland, unfavorable weather patterns and problems of pests and diseases. These emphasize that the quality of advisory services is not the only important factor influencing technology adoption and productivity, and the need for complementary progress in other areas, especially development of the rural financial system. Implications are drawn for enterprise targeting and ensuring sustainability of improvements in productivity, as well as for designing and implementing service provision programs in other parts of the Uganda and in other countries.